The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/6383526
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Tibial Osteomyelitis after Anterior Cruciate Ligament Reconstruction with Hamstrings Autograft and Bioabsorbable Interference Screw: A Case Report and Review of the Literature

Abstract: Osteomyelitis following arthroscopically assisted anterior cruciate ligament (ACL) reconstruction has rarely been reported in the literature. We report a case of a 20-year-old female who had delayed tibial osteomyelitis and a pretibial cyst with culture-positive, oxacillin sensitive Staphylococcus epidermidis 15 months after an ACL reconstruction with hamstring autograft. Soft tissue fixation within the tibial tunnel was with a poly-L-D-lactic acid (PLDLA) bioabsorbable interference screw. The patient underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…Development of infection after ACL reconstruction is extremely rare, however, it sometimes induces severe knee dysfunction [4] , [7] . Treatment of infection can be accomplished by early debridement, constant joint irrigation, long-term intravenous antibiotics, graft retention, or removal [1] , [2] , [5] , [8] . The most frequently used treatment is joint irrigation and debridement with graft retention [9] , [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of infection after ACL reconstruction is extremely rare, however, it sometimes induces severe knee dysfunction [4] , [7] . Treatment of infection can be accomplished by early debridement, constant joint irrigation, long-term intravenous antibiotics, graft retention, or removal [1] , [2] , [5] , [8] . The most frequently used treatment is joint irrigation and debridement with graft retention [9] , [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested immediate removal of the infected ACL graft [3] , [11] , [12] , but others advocated ACL graft removal only in cases of persistent infection [2] , [13] . Aggressive surgical debridement combined with proper antibiotics according to the isolated pathogen is thought to be the key to effective treatment in cases of persistent infection [3] , [5] , [8] , [12] . This case is an extremely miserable case of prolonged infection after ACL reconstruction with a fistula for two years despite complete removal of the metal implant and debridement of necrotic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Late phase foreign body reactions have been reported following biomaterial use both in the early and late postoperative phase 39,40 . Both Waris et al 4 and Givissis et al 25 evaluated the use of third generation synthetic biodegradable screws in metacarpal fractures, finding postoperative tissue reactions presented in a delayed manner.…”
Section: Discussionmentioning
confidence: 99%
“…The most common infection in ACL reconstruction is septic arthritis, and as such the approach is thorough debridement, and removal of infected graft. Though favourable outcomes have been described with graft retention after removal of implants for those who developed septic arthritis, a protocol for tibial tunnel osteomyelitis has yet to be elaborated 5 16 17. The common causative organisms for infection as a sequelae of ACL reconstruction include Staphylococcus , Peptostreptococcus , Enterococcus and fungal species 16…”
Section: Discussionmentioning
confidence: 99%